Mountains and their ecotones increase landscape heterogeneity and maintain a unique assemblage of grasshoppers in the southern Kalahari. (7th December 2022) - van der Mescht, Aileen C.; Codron, Daryl
Abstract: South Africa is a megadiverse country. Here, natural communities are unevenly distributed across, and within, seven distinct biomes. In such heterogeneous landscapes, understanding spatial patterns of biodiversity is essential for planning and implementing efficient conservation measures. The southern Kalahari, forming part of South Africa's savanna biome, is an arid region of peculiarly high diversity and endemism. The responses of orthopteran assemblages to changing environmental conditions across the Kalahari were investigated by comparing alpha and beta diversity levels across discrete vegetation types in the Tswalu Kalahari Reserve. The degree of association between species and specific vegetation types were also studied and how a key life history trait ‐ dispersal ability – influences community composition was determined. This study identified 46 grasshopper species within the reserve, which compares well with richness levels in other more productive habitats of the country. Local (alpha) diversity was higher in mountain and mountain‐ecotone sites versus vegetation types on the plains, and species turnover was also exceptionally high – approaching 100% ‐ across these two groups. The few (3) dispersal limited species recovered were associated only with the mountain‐ecotone group, with emergent dominance patterns suggesting that competitive rather than dispersal abilities determine the species composition of unique assemblages in the landscape. Topology plays a key role in maintaining spatial diversity across the southern Kalahari landscape. Mountains, and their ecotones, promote not only species turnover, but also richness and functional diversity. These can be viewed as islands of diversity, and should be targeted priority areas for conservation beyond the boundaries of protected areas. Abstract : Topology plays a role in maintaining spatial diversity across the southern Kalahari landscape. Mountains maintain a unique assemblage of grasshoppers than those of the plains. Exceptionally high rates of turnover exist between mountains and plains vegetation types.